The Policy Implementation of Simplification Bureaucracy For Performance Improvement In The Ministry of Administrative And Bureaucratic Reform - Sipayung, Naptalina; Sumaryadi, I Nyoman; Daraba, Dahyar; Lukman, Sampara (Devotion : Journal of Research and Community Service, 2022)
The bureaucratic simplification policy is a direct direction from the President and that policy was the first policy which changed structure massively form structure to functional. Ministry of Administrative and Bureaucratic Reform as a pilot project for that policy implementation. This research aims to know The Policy Implementation of Simplification Bureaucracy For Performance Improvement in The Ministry of Administrative and Bureaucratic Reform and whats is the problems that opportunities and challenges the policy implementation of Simplification bureaucracy for Performance Improvement and what is the ideal model for Bureaucratic Simplification and then find what is the ideal models for optimize policy implementation. This research focuses on functional officers who were transferred from structural officers to functional) and locus in the Ministry of Administrative and Bureaucratic Reform. Research design uses qualitative with description approach. The object of this research is a number of 141 officer structure which transferred to functional (52 from echelon 3 and 89 echelon from 4). Data is obtained by using interview, observation and documentation study from 35 informants . Primary data that was obtained by interview and processed with analyzes on theory Policy Implementation by Edwards George III 1980, Theory and Simplification Bureaucracy with Guollart & Kelly with Development Organization Theory and for increasing performance using Cascio Theory 1992. All primary data especially from interview put in to coding with each informant as formulation regulator (Echelon I), implementor (echelon II) and target group (functional from echelon 3 and 4), but cause of the covid situation, part of officers work from home, I do less observation but do in deep interview via zoom. The result finds that the implementation policy of simplification bureaucracy has not optimize yet in accordance with the goals and objectives or has not brought significant changes especially in increasing performance. To do implementation for this policy needs another policy (lack of policy) especially for reward and punishment, performance appraisal, work mechanism) and changed culture organization (mindset and culture set).